Weber’s Understanding of Epistemological and Methodological Foundations of Social Sciences and Sociology - Mandić, Stefan V. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
Since the formation of sociology as a separate science during the first half of the 19th century, some of the most important questions that sociologists have attempted to answer have been what the cognitive possibilities of sociology as a science are and what the most adequate methods of research that it should use are. In this work, we will critically analyze how Max Weber, one of the most significant sociologists, understood the cognitive possibilities of sociology and what method, according to him, sociology as a social science should use. Firstly, we will examine how the intellectual climate of the second half of the 19th century influenced his understanding of scientific methodology in a broader sense. Then, Weber’s vision of the basic epistemological characteristics of social sciences and his methodological-theoretical determination of sociology will be presented.
Keywords: Max Weber; social sciences; sociology; epistemology; methodology